Free vibration of a cracked double-beam carrying a concentrated mass - Khoa, Nguyen Viet; Quang, Nguyen Van (Vietnam Journal of Mechanics, 2016)
This paper presents the free vibration of a cracked double-beam carrying a concentrated mass located at an arbitrary position. The double-beam consisting of two different simply supported beams connected by an elastic medium is modelled by using finite element method. The influence of the concentrated mass on the frequencies and mode shapes is investigated. The relationship between the natural frequency and the location of concentrated mass is established and related to the mode shapes. The numerical simulations show that when there is a crack, the frequency of the double-beam changes sharply when the concentrated mass is located close to the crack position. This sharp change can be amplified by wavelet transform and this is useful for crack detection. The crack location can be determined by the location of peaks in the wavelet transform of the relationship between frequency and mass location.